Economics of Crop Rotations With and Without Carinata for Sustainable Aviation Fuel Production in the SE United States - Karami, Omid; Dwivedi, Puneet; Lamb, Marshall; Field, John L. (Frontiers in Energy Research, 2022)
In 2019, the aviation sector in the United States emitted 255 million metric tons of carbon dioxide (CO2) emissions, i.e., about five percent of the total domestic CO2 emissions from the energy sector. The sustainable aviation fuel (SAF) derived from carinata (Brassica carinata) could reduce CO2 emissions of the aviation sector in the United States. Therefore, it is important to estimate changes in farm economics with and without carinata for ascertaining its production feasibility. In this context, the current study first assesses a combination of 12 popular rotations of corn, cotton, peanut, and soybean with winter crops of winter wheat and carinata in South Georgia over four years. Then, the net present values (NPVs) of 292 feasible cropping systems over four years are calculated. Finally, this study develops a risk model for ascertaining the probability distributions of NPVs for selected cropping systems subject to uncertainties related to prices and yields of selected summer and winter crops. Carinata in the corn-corn-soybean rotation has the highest NPV ($2,996/ha). The least risky rotation is cotton-cotton-peanut, with a 58.9% probability of a positive NPV. Carinata can decrease the risk level of crop rotations by 8.1%, only if a contract price of $440.9/tis offered. Therefore, a risk averse, risk neutral, or risk acceptant farmer can potentially include carinata in the rotation. Overall, carinata would increase the profitability of farm operations and decrease risk in the SE United States, and therefore, a high likelihood exists, that farmers would adopt it for meeting the growing demand for SAF in the United States.